Enhancement of symmetry-induced photoluminescence in bismuth tungstate microcrystals - Rocha, Poliana Lima; Batista Barbosa, Diego Augusto; de Oliveira Lima, José Renato; Piedade Prazeres, Gilza Maria; de Araujo Paschoal, Carlos William; Li, Maximo Siu; Longo, Elson [UNESP]; Maciel, Adeilton Pereira; Almeida, Marcio Aurélio Pinheiro (Elsevier, 2016)
Bi2WO6 (BWO) powders synthesized via hydrothermal processes were studied in order to determine the effect of structure on photoluminescence (PL). BWO samples were characterized using X-Ray Powder Diffraction, UV–vis diffuse reflectance, field emission scanning electron microscopy, and PL intensity measurements. Orthorhombic structures were observed in all samples. A change in crystal microstructure and optical band gap was observed. The PL intensity obtained with different samples varied, with the highest intensity obtained with BWO fabricated with polyvinylpyrrolidone (PVP). Using Raman spectroscopy, a change in the microcrystal symmetry from P21ab to B2cb was observed and found to be responsible for the increase in photoluminescence.
Keywords: Bismuth tungstate; Photoluminescence; Structural change